The impact of social comparison, fear of missing out, and online social network usage on self- esteem among Malaysian youth - Ma’rof, Aini Azeqa; Abdullah, Haslinda (Human Resources Management Academic Research Society (HRMARS), 2024)
This study examines the relationship between social comparison, Fear of Missing Out (FoMO), online social network usage, and self-esteem among Malaysian youth. Using a sample of 420 youth, the research utilizes quantitative methods, including Pearson correlation and multiple regression analyses, to explore the predictive effects of these factors on self-esteem. The results reveal that social comparison is the strongest negative predictor of self-esteem, followed by FoMO and online social network usage. Higher levels of social comparison, FoMO, and online social network usage were significantly associated with lower self-esteem. These findings underscore the growing impact of social media on youth's psychological well-being and highlight the need for interventions focused on reducing social comparison, managing FoMO, and promoting healthy social media habits. This study offers valuable insights for educators, policymakers, and mental health practitioners aiming to improve youth self- esteem and digital well-being.